Order-Controllable Cylindrical Vector Vortex Beam Generation by Using Spatial Light Modulator and Cascaded Metasurfaces - Yanliang He; Huapeng Ye; Junmin Liu; Zhiqiang Xie; Xiaoke Zhang; Yuanjiang Xiang; Shuqing Chen; Ying Li; Dianyuan Fan (IEEE Photonics Journal, 2017)
Cylindrical vector vortex (CVV) beam, which possesses both helical phase front and spatially inhomogeneous polarization, is a promising structured light for its various applications ranging from optical communication to optical field manipulation and optical microscopy. However, approaches to generate CVV beams with switchable and tunable polarization order and topological charge are still immature, which hinders the wide application of CVV beams. In this paper, we have experimentally demonstrated that order-controllable CVV beams can be produced by using spatial light modulator (SLM) and equivalent q-plate system at wavelength of 1550.8 nm. It is shown that the topological charge of the CVV beam can be switched by directly programming the SLM. We have also demonstrated that the polarization order of the CVV beam can be tuned to as high as eight by employing an equivalent q -plate system, which consists of two cascaded metasurfaces and a half-wave plate. To further verify the helical phase of the CVV beam, we have proposed a novel measurement method based on first removing the vector property and then interfering the remaining helical phase with plane wave or spherical wave.